A numerical study and proposed design rules for stress concentration factors of stainless steel hybrid tubular K-joints. (15th April 2021) - Feng, Ran; Tang, Chi; Chen, Zhenming; Roy, Krishanu; Chen, Boshan; Lim, James B.P.
Highlights: A FE investigation on SCFs of stainless steel CHS-to-SHS and SHS-to-CHS K-joints was conducted. An extensive parametric study comprising 324 FEMs was conducted. CIDECT Design Guidelines were not suitable for predicting the SCFs of the hybrid K-joints. The proposed design equations could accurately predict the SCFs of such stainless steel hybrid K-joints. Abstract: This paper presents a finite-element analysis (FEA) of the stress concentration factors (SCFs) of stainless steel hybrid tubular K-joints with square braces and circular chord and K-joints with circular braces and square chord. The developed finite-element (FE) models include material non-linearities and are validated against corresponding experimental results available in the literature. The validated FE models were used to conduct an extensive parametric study comprising 324 FE models. The critical geometric parameters of the parametric study include: brace width-to-chord diameter ratio ( β 1  =  b 1 / d 0 ), brace-to-chord thickness ratio ( τ  =  t 1 / t 0 ), chord diameter-to-thickness ratio (2 γ 1  =  d 0 / t 0 ), brace diameter-to-chord width ratio ( β 2  =  d 1 / b 0 ), chord width-to-thickness ratio (2 γ 2  =  b 0 / t 0 ), eccentricity ( e ), gap distance ( g ) of K-joints with gap, and overlap ratio ( Ov ) of overlapped K-joints. The results of the parametric study show that the effect of β on the SCF varies for different types of K-joints. For all hybrid tubular K-joints, the values of SCFs increases with an increase in 2 γ value. For gapped K-joints, the values of SCFs increases with an increase in e value. An attempt was made to compare the numerical results against the SCFs calculated in accordance with International Committee for the Development and Study of Tubular Structures (CIDECT) (2001) for both the stainless steel hybrid tubular K-joints with square braces and circular chord and K-joints with circular braces and square chord. This comparison reveals how the design equations available in CIDECT (2001) for pure circular and square tubular joints are not suitable for predicting the SCFs of both the stainless steel hybrid tubular K-joints with square braces and circular chord and K-joints with circular braces and square chord. Therefore, improved design equations are proposed in this paper for predicting accurately the SCFs of stainless steel hybrid tubular K-joints with square braces and circular chord, as well as circular braces and square chord.